Sensitive electrochemical determination of unlabeled MutS protein and detection of point mutations in DNA - Palecek, Emil; Masarík, Michal; Kizek, Rene; Kuhlmeier, Dirk; Hassmann, Jörg; Schülein, Jürgen (Analytical chemistry, 2004)
MutS protein plays an important role in the DNA repair system in prokaryotic and eukaryotic cells; it recognizes unpaired and mispaired bases in duplex DNA and can be used for detection of point mutations in vitro. We have shown that small amounts of this protein can be detected electrochemically at mercury and carbon electrodes without any labeling. Using constant current stripping analysis (CPSA) and mercury electrodes, tens of attomoles of this protein can be detected. The sensitivity of the determination at carbon electrodes is by more than 3 orders of magnitude lower. Using biotinylated DNA duplexes attached to magnetic beads, single-base mismatches and insertion/deletions were recognized by MutS. Picogram amounts of this protein were detected by CPSA after MutS releasing from the beads.
Keywords: katalýza; DNA, Bacterial; Protein Binding; uhlík; Hydrogen; Sensitivity and Specificity; Catalysis; Point Mutation; bodová mutace; MutS DNA Mismatch-Binding Protein; Oxidation-Reduction; rtuť; tyrosin; vodík; DNA bakterií; Carbon; Electrochemistry; Mercury; Tyrosine; Thermus; vazba proteinů; senzitivita a specificita; vazebný protein MutS opravné syntézy DNA; oxidace-redukce; elektrody; elektrochemie; Electrodes